2015
DOI: 10.1111/bcp.12499
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of thiazide‐induced hyponatraemia: time to reconsider electrolyte monitoring regimens after thiazide initiation?

Abstract: AimsHyponatraemia is one of the major adverse effects of thiazide and thiazide-like diuretics and the leading cause of drug-induced hyponatraemia requiring hospital admission. We sought to review and analyze all published cases of this important condition.MethodsOvid Medline, Embase, Web of Science and PubMed electronic databases were searched to identify all relevant articles published before October 2013. A proportions meta-analysis was undertaken.ResultsOne hundred and two articles were identified of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 120 publications
2
52
1
4
Order By: Relevance
“…Overall, 10% of TAH patients were neither subjected to thiazide withdrawal nor received any active hyponatremia therapy. Hyponatremia frequently appears months or even years after the initiation of a thiazide diuretic, presumably as a consequence of acute development of a concurrent disorder, such as gastroenteritis or worsening heart failure, that led to the perturbation of a formerly stable steady state in which dietary intake matched water and solute losses [9]. Under these circumstances, the ensuing deterioration of osmotic homeostasis is often severe and potentially life threatening [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 10% of TAH patients were neither subjected to thiazide withdrawal nor received any active hyponatremia therapy. Hyponatremia frequently appears months or even years after the initiation of a thiazide diuretic, presumably as a consequence of acute development of a concurrent disorder, such as gastroenteritis or worsening heart failure, that led to the perturbation of a formerly stable steady state in which dietary intake matched water and solute losses [9]. Under these circumstances, the ensuing deterioration of osmotic homeostasis is often severe and potentially life threatening [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, female gender, and low body mass index have been identified as risk factors for hyponatremia in thiazide-treated patients [4,6,8]. Usually, hyponatremia ensues within days after the initiation of treatment and the average time from initiation to diagnosis was calculated to be 19 days in a recent meta-analysis [9], but onset can be delayed by months [10,11]. True TIH seems to be dose-independent and probably occurs only in a susceptible subpopulation of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Both hypokalemia and hyponatremia occurred consecutively in 07 patients (17.5%). Studies suggest that thiazide-induced hyponatremia occurs within 1 dayto a median time of one year of drug initiation 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…30 another review reported that when compared to other antihypertensive therapy, both thiazidelike and thiazide-type diuretics showed a similar number of adverse events in patients with comparable reductions in blood pressure. 4 …”
Section: Discussionmentioning
confidence: 99%